(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Diagnosis, treatment and prevention of diseases of the oral mucosa (OBSHQ) occupy an important place among the current problems of modern dentistry. The mucous membrane of the oral cavity is one of the most important systems of the body and acts as a barrier (barrier) against the effects of pathogenic biological, physical and chemical factors. The localization of the mucous membrane of the oral cavity is significantly different from other mucous membranes both morphologically and histochemically, however, as a result of acute or chronic mechanical damage, thermal, radiation or chemical effects, the oral cavity Pathological diseases develop in the mucous membrane. In the development of diseases of the mucous membrane of the oral cavity, viral and bacterial infectious agents are also the cause. In addition, the state of specific and non-specific resistance of the organism is of great importance. Changes in the mucous membrane of the oral cavity are typical for hypovitaminosis, diseases of blood and hematopoietic organs, endocrine, cardiovascular systems, digestive organs, skin, kidneys, acute infectious and systemic diseases. In her research, I.V. Firsova emphasizes that salivary dysfunction is an important factor in the pathogenesis and clinical symptoms of mucous membrane diseases, especially in patients with combined pathologies of the digestive, cardiovascular, endocrine and other systems. ladi It is noted that long-term treatment with xerogenic drugs also caused changes in the mucous membrane of the oral cavity. . Increasing the specialist’s knowledge and skills in the field of identifying and then identifying a pathological focus, not only visual observation of its morphological elements, but also helps to know its exact description in the history of the disease.